THE REPLICATION EFFICIENCY OF DENGUE VIRUS SEROTYPE 1 ISOLATED FROM PATIENTS WITH DENGUE FEVER IN HUMAN HEPATOCYTE CELL LINES - GENI , Lenggo; WIDODO, Lovendo Ilham; SWESTIKAPUTRI, Chrecentia Hanna; SYAHRURACHMAN, Agus; DEWI, Beti Ernawati (African Journal of Infectious Diseases (AJID), 2025)
ABSTRACT Background. The Efficiency of viral replication in cells depends on the capability of supporting virus replication by the cells. We characterized the effectiveness of Dengue Virus Serotype 1 (DENV-1) replication in various cell lines and various multiplicity of infection (MOI) starting from 2 FFU/cell up to 0,3125 FFU/cell. Material and Methods. We used HepG2 and Huh-7 human hepatocyte cell lines and in addition, we also used nonhuman kidney cells (Vero cells). DENV-1 strain IDS 11/2010 was isolated from DF patients and previously propagated in Huh7 and Vero cells as DENV-1-adapted Huh-7 and DENV-1-adapted Vero cells, respectively. Huh7 cells, Hep G2 cells, and Vero cells were infected with DENV-1 at various MOI and incubated for 48 hours at 370C with 5% CO2. DENV-infected cells were determined by indirect immuno-peroxidase staining using 3,3’-Diaminobenzidine (DAB). DENV-1 infected cells as foci were counted under inverted light microscopy and were used to determine the virus titer. Result. The virus was adapted to Huh-7 and Vero cells, with results showing that Vero cells exhibited the highest replication efficiency, evidenced by significant viral titers. Among human hepatocyte cell lines, DENV-1 demonstrated greater replication in Huh-7 cells than in HepG2 cells. Notably, no foci formation was observed in HepG2 cells after 48 hours of infection. Conclusion. These findings underscore the suitability of Vero and Huh-7 cells as optimal environments for DENV-1 replication, offering valuable insights for enhancing laboratory diagnostics and advancing antiviral strategies and vaccine development against DENV-1. Keywords: Huh-7, HepG2, Vero, DENV-1, Efficiency, Replication